Heterostructure ohmic contacts to p-CdTe polycrystalline films - Sukach, A.V.; Tetyorkin, V.V.; Tkachuk, A.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Heterostructure contacts p⁺ -PbTe/p-CdTe were prepared using the hot-wall technique on glassceramic substrates. It has been shown that the potential barrier at the p⁺ -PbTe/p-CdTe interface is not formed in the case of heavily doped lead telluride. That allows one to create ohmic heterocontacts of metal-p⁺ -PbTe/p-CdTe type. The transverse and in-plane transport of carriers has been investigated as a function of bias voltage and temperature. The current-voltage characteristics measured for the transverse arrangement of contacts exhibited ohmic behavior. The current-voltage characteristics of these contacts are determined by unipolar injection of holes from p⁺ -PbTe into p-CdTe. The inplane transport has been explained by presence of potential barriers at the grain boundaries. The potential barrier height has been estimated to be ~0.1 eV at room temperature. The mechanism of carrier transport is thermionic emission.